Religiosity in the Digital Era and the Challenges of Hoaxes, Post-Truth and Radicalism on Social Media - Setia, Paelani; Dilawati, Rika (UIN Sunan Gunung Djati Bandung, 2024)
In the era of globalization and advances in information technology, social media plays a key role in shaping the dynamics of people's daily lives. This phenomenon not only affects social and economic aspects but also penetrates the diverse dimensions of religious life. This article examines the impact of social media on people's religiosity, specifically in context post-truth and hoaxes. There is a trend where urban people prefer to get religious understanding from ustaz/clerics on social media rather than from traditional religious authorities. Freedom of expression on social media, without an adequate selection process and credibility, creates a diversity of interpretations that can confuse the public. The rise of hoaxes and information post-truths on social media poses a serious challenge to quality religious understanding and traditional religious authority. This article highlights the potential for religious disintegration and radicalism as a result of hoax information and post-truth on social media. Through a qualitative approach and case studies, this research explores the transformation of religious paradigms, freedom of expression, and the diversity of interpretations that occur on social media. This article suggests efforts to verify information and increase media literacy as a solution to overcome the negative impact of social media on people's religiosity.